2006
DOI: 10.1128/iai.01885-05
|View full text |Cite
|
Sign up to set email alerts
|

SdrI, a Serine-Aspartate Repeat Protein Identified in Staphylococcus saprophyticus Strain 7108, Is a Collagen-Binding Protein

Abstract: A gene encoding a serine-aspartate repeat protein of Staphylococcus saprophyticus, an important cause of urinary tract infections in young women, has been cloned and sequenced. In contrast to other SD repeat proteins, SdrI carries 21 additional N-terminal repeats with a consensus sequence of (P/A)ATKE(K/E)A(A/V )(T/I)(A/T/S)EE and has the longest SD(AD) (1-5) repetitive region (854 amino acids) described so far. This highly repetitive sequence contains only the amino acids serine, asparagine, and a distinctly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
46
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 46 publications
(93 reference statements)
1
46
1
3
Order By: Relevance
“…Likewise, strain 7108 was not killed by complement-mediated opsonophagocytosis, suggesting that it produced CP; however, strain 7108 exhibited HA under both anaerobic and aerobic conditions (HA index, Յ2). Besides UafA, S. saprophyticus 7108 produces several additional surface-associated proteins: Ssp (a lipase) (53), SdrI (a collagen binding protein) (52), and Aas (a multifunctional protein with autolysin activity, adherence to fibronectin and uroepithelial cells, and HA activity) (14,15,17,35). The presence of a second protein with HA activity (lacking in ATCC 15305) may explain the discrepancies observed between the phagocytic assay and HA for strain 7108.…”
Section: Vol 192 2010 S Saprophyticus Capsular Polysaccharide 4623mentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, strain 7108 was not killed by complement-mediated opsonophagocytosis, suggesting that it produced CP; however, strain 7108 exhibited HA under both anaerobic and aerobic conditions (HA index, Յ2). Besides UafA, S. saprophyticus 7108 produces several additional surface-associated proteins: Ssp (a lipase) (53), SdrI (a collagen binding protein) (52), and Aas (a multifunctional protein with autolysin activity, adherence to fibronectin and uroepithelial cells, and HA activity) (14,15,17,35). The presence of a second protein with HA activity (lacking in ATCC 15305) may explain the discrepancies observed between the phagocytic assay and HA for strain 7108.…”
Section: Vol 192 2010 S Saprophyticus Capsular Polysaccharide 4623mentioning
confidence: 99%
“…Gatermann et al showed that in a rodent model of ascending UTI, the production of urease contributes to S. saprophyticus growth and pathogenicity in the bladder (10,12). Other putative virulence factors of S. saprophyticus include a surface-associated lipase (11,51,53), the collagen binding protein SdrI (52), and a cell wall-anchored hemagglutinin protein that mediates the binding of S. saprophyticus to sheep erythrocytes, fibronectin, and human uroepithelial cells (14,29,34,35). The hemagglutinin was dubbed UafA in the sequenced ATCC 15305 strain, and deletion of the uafA gene resulted in reduced S. saprophyticus hemagglutination (HA) and adherence to human bladder carcinoma cells (29).…”
mentioning
confidence: 99%
“…SD repeats tether the N-terminal ligand-binding domains to the C-terminal LPXTG sorting signal, which triggers sortase A-mediated linkage to the cell wall envelope (20 -22). SD repeat proteins are also found in other pathogenic staphylococci, for example the opportunistic pathogen Staphylococcus epidermidis (23) and Staphylococcus saprophyticus, a frequent cause of urinary tract infection (24).…”
mentioning
confidence: 99%
“…A second protein, urease, is important for efficient colonization of the bladder and kidneys, for inflammation in the bladder, and for dissemination to the spleen in a rat model of UTI (5). Several other putative virulence factors have been characterized in vitro, including extracellular slime; lipoteichoic acids, which are implicated in adherence to urothelial cells (4); a cell wall-anchored protein (UafA) that may act as an adhesin for bladder cells (4, 22); a surface-associated lipase (Ssp) that forms fimbria-like surface appendages (6, 37); and a surface-associated collagen-binding protein (SdrI) that shares sequence and structural homology with the adhesive Sdr proteins of Staphylococcus aureus and Staphylococcus epidermidis (36,45).A major limitation in assessing the contributions of S. saprophyticus virulence factors to pathogenesis is the lack of a well-characterized in vivo model. However, an enterococcal UTI mouse model has been described in which E. faecalis displays a tropism for the kidney, where it can persist for at least 2 weeks (21, 42).…”
mentioning
confidence: 99%